SELF-CLEANING GLASS BASED ON ACID-TREATED Ti02 FILMS WITH PALMITIC ACID AS MODEL POLLUTANT = Self-cleaning Kaca Berbasls Lapis Tlpls TIOzdengan Perlakuan Asam dan Asam Palm/tat sebagal Model Polutan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Preparation and characterization of seif-cleaning glass based on acid-treated Ti02 films as well as evaluation on their self-cleaning properlies have been carried. out. Palmitic acid photodegradation was used as model pollutant. Acid-treated Ti02 powders were deposited on glass surface by using spraying technique. The XRD results showed that acid-treated Ti02 film exhibited decreased anatase crystalline size. The cOffesponding SEM images shC!wedporous surface morphology. Layer densification was obseNed as the film thickness increased. TtO:z photocatalytic activity increased as the length of UV radiation increased. Best results were obtained at experimental condition of 35 hours UVradiation time. It is also obseNed that the thickness of Ti021ayers influenced the efficiency of palmitic acid photodegradation. The film with 1.661pm thick Ti021ayers and 6.933 mg weight (0.7164 mg/cnf) could degrade 97.54 %mg palmitic acid/cm2thin film. Keywords: Ti02 films, acid treatment, self-cleaning glass